Canine soft tissue sarcomas: the expression of RUNX2 and karyopherin alpha-2 in extraskeletal (soft tissues) and skeletal osteosarcomas - Leonardi, Leonardo; Manuali, Elisabetta; Bufalari, Antonello; Porcellato, Ilaria (Frontiers in Veterinary Science, 2024)
Extraskeletal osteosarcoma (EOS) is a malignant tumor producing bone matrix and/or chondroid material, without direct attachment to bone or periosteum. In humans and dogs, EOS is highly infiltrating, rapidly growing, often characterized by osteoid deposition and variable ossification, similar to primary skeletal osteosarcoma (SOS). In dogs, EOS arises from visceral and soft tissue locations, occasionally in trauma or foreign body sites, or in granulomas. Few data are currently available on the phenotype of these tumors. The present study aims to assess the expression RUNX2 and Karyopherin alpha-2 in EOS, comparing it with SOS and the data available from the human counterpart. Seventeen cases of canine osteosarcoma (13 EOS and 4 SOS) were retrospectively selected and submitted to immunohistochemistry for RUNX2 and Karyopherin alpha-2. Our results showed that, in EOS, RUNX2 is expressed in a mean of 73.07 ± 5.36 neoplastic cell nuclei, in face of a mean 36.15 ± 6.25 of Karyopherin alpha-2 positive nuclei. Osteoclasts, when present, were negative for both markers. No correlation was observed among the two markers (p > 0.05), nor statistically significant difference in quantitative expression was assessed comparing EOS and SOS groups. RUNX2 is expressed in canine EOS similarly to SOS and could be used as a diagnostic marker in a larger panel. Karyopherin alpha-2 is expressed in canine EOS and SOS similarly to human SOS and could be validated in future studies as an additional diagnostic marker. Further studies should be planned to evaluate the expression of these proteins as prognostic predictive parameters.